Pengaruh Citra Destinasi dan E-Wom terhadap Keputusan Berkunjung Wisatawan melalui Minat Berkunjung sebagai Variabel Mediasi - Roring, Ferdy; Ferdinand Johanes Tumewu; Dringhuzen Jekke Mamahit (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2025)
This study aims to analyze the influence of destination image and electronic word of mouth (e-WOM) on tourists' visit decisions, with intention to visit as a mediating variable in East Bolaang Mongondow Regency. The study used a quantitative approach with a survey method of 100 tourists selected using an accidental sampling technique. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) to test the validity, reliability, and relationships between variables in the research model. The results of the analysis showed that all constructs met the criteria of convergent validity, discriminant validity, and good reliability. Destination image had a positive and significant effect on tourists' visit intentions and visit decisions. E-WOM had a positive and significant effect on visit intentions, but did not directly influence visit decisions. Intention to visit was proven to have a very significant effect on visit decisions and acted as a strong mediator in the relationship between destination image and e-WOM on visit decisions. The high R-square value indicates that the model has strong explanatory power in explaining tourist visit behavior. The conclusion of this study confirms that intention to visit has a strategic role as a mediator in shaping tourists' visit decisions. Therefore, destination managers need to strengthen their destination image and optimize e-WOM-based digital promotion strategies to increase tourists' decision to visit. Keywords: Destination Image, E-Worm, Tourism, Visit Decision, Visit Intention.